2014
DOI: 10.1109/tit.2014.2322859
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Bounds for Relay Channels With Intersymbol Interference and Colored Gaussian Noise

Abstract: The capacity of a relay channel with inter-symbol interference (ISI) and additive colored Gaussian noise is examined under an input power constraint. Prior results are used to show that the capacity of this channel can be computed by examining the circular degraded relay channel in the limit of infinite block length. The current work provides single letter expressions for the achievable rates with decodeand-forward (DF) and compress-and-forward (CF) processing employed at the relay. Additionally, the cut-set b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Para demonstrar tais expressões, assim como foi feito em [5], considera-se o número de subcanais N → ∞. Desta forma, o single relay channel pode ser modelado como um Linear Gaussian Relay Channel (LGRC) [6].…”
Section: Capacidade Teóricaunclassified
“…Para demonstrar tais expressões, assim como foi feito em [5], considera-se o número de subcanais N → ∞. Desta forma, o single relay channel pode ser modelado como um Linear Gaussian Relay Channel (LGRC) [6].…”
Section: Capacidade Teóricaunclassified
“…We use notations and formulations similar to [3] and [4]. We use * and ⊛ to denote the linear and circular convolution, respectively.…”
Section: Definitions and Channel Modelmentioning
confidence: 99%
“…Goldsmith and Effros [3] obtained the capacity region of a finite-memory broadcast channel (BC) with ISI and colored Gaussian noise and showed that this capacity region is equal to the capacity region of an n-circular Gaussian BC as n grows to infinity. Recently, Choudhuri and Mitra [4] derived single-letter expressions for the achievable rates and an upper bound on the capacity of a relay channel with ISI and additive colored Gaussian noise.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of ISI arose with the early attempts at telegraph transmission in the mid-nineteenth century. Since that time, the problem has been considered from many viewpoints [20,21,[139][140][141][142][143][144][145][146][147][148][149][150]. For example, in [139], a method for specifying an optimum linear, time invariant receiving filter for a digital data transmission system was derived, assuming that the transmission medium introduces intersymbol interference and additive Gaussian noise, while, in [140], the impact of ISI on the error performance in binary differentially-coherent phase-shift-keying (PSK) systems was evaluated.…”
Section: Intersymbol Interferencementioning
confidence: 99%
“…The influence of ISI in the capacity region of broadcast channels in the presence of colored Gaussian noise was studied in [146], whereas the impact of ISI on the capacity of frequency-selective channels in training-based transmission schemes was presented in [144]. Furthermore, the impact of ISI and additive colored Gaussian noise on the capacity of relay channels was examined in [147]. In [148], the authors presented the impact of ISI on the performance of diversity systems with multiple branches, in the presence of multipath Rayleigh, Nakagami-m and Rician fading.…”
Section: Intersymbol Interferencementioning
confidence: 99%